Vindicating the commercial republic The Federalist on union, enterprise, and war - Peacock, Anthony A. (Anthony Arthur), 1959- (Lexington Books, 2018)
"Contrary to most academic commentary on The Federalist, this book contends that the most significant teachings of the work did not have to do with the institutions of government so much as with the non-institutional features of American constitutionalism, specifically its advocacy for greater union, the development of an unparalleled culture of enterprise, and provision for war. Key to understanding why these features were so critical to The Federalist is the work's rejection of classical liberalism's orthodoxy that commercial republics were moderate or pacific in nature rather than spirited, enterprising, and warlike. Using the ancient historian Thucydides account of the daring, innovation, and restlessness of ancient commercial Athens as an interpretive guide for the commercial republican theory that The Federalist embraces, this book provides a sweeping reinterpretation of American constitutionalism. At the heart of The Federalist's teaching, Peacock contends, is the intention to create an innovative and spirited culture of enterprise that will not only inform America's civil character post-1787 but its military character as well. No scholarship has considered the significance of Thucydides to the The Federalist. This book does in a comprehensive reconstruction of the work that concludes that The Federalist anticipates as well as any text on American constitutionalism what many consider to be the most definitive features of American character today: its spirit of enterprise and its qualified willingness to engage in war for both reasons of national interest and republican principle" --